Horizontal Bone Augmentation in the Mandible by Subperiosteal Tunneling Technique: Case Report - DE SOUZA, VILTON; Schoenberger, Emilly; Francisco Wesoloski, Roberto; Garcia, Gislaine; Rosalen da Silva, Rosalen; Manfro, Rafael (International Journal of Innovative Research in Medical Science, 2023)
Bone augmentations for installation of dental implants are often necessary and often decreases patient acceptance of treatment due to increased morbidity. In this clinical case, we report the procedure of subperiosteal tunneling (tunnel technique) combining in situ xenogeneic graft, of slow absorption bovine origin, for horizontal augmentation in the mandible. Bone grafts, horizontal and vertical, are extremely important procedures for oral rehabilitation in implant dentistry, thus enabling the re-establishment of an adequate framework for the installation of implants with correct positioning, restoring function and aesthetics to our patients. The most commonly used therapy consists of raising a more invasive flap to expose the bone tissue and performing associated grafting techniques. However, in well-indicated cases, we have this tool at our disposal, where we can treat our patients with minimally invasive techniques, such as subperiosteal tunneling, with very favorable clinical results. The main advantage of this approach, in addition to the minimally invasive technique, is the preservation of the periosteum and blood supply to the flap, which may contribute to increased favorable wound healing and a reduced risk of flap dehiscence and membrane exposure. This tunnel approach to guided bone regeneration in horizontal bone gains, specifically adapted and filled with xenogeneic bone, resulted in a significant gain in bone volume in thickness, which allowed implant placement (average increase of 5.0mm observed on tomography). As for morbidity, the patient reported a better postoperative period in the reconstruction surgery compared to the implant installation surgery, measured by the visual analogue scale (VAS).